Citizenship as a Fundamental Right - Aranha, Stephen B. (International Journal of Bahamian Studies, 2015)
This article looks at the way the Constitution of the Commonwealth of The Bahamas in its chapter on citizenship combines elements of both ius solis as well as ius sanguinis but fails to apply either of these principles consistently. This can result in the de iure statelessness of children born to Bahamian parents overseas, and in the de iure and/or de facto statelessness of children born in The Bahamas to non-Bahamian parents. The article further analyses the proposals for amendments to the Constitution as presented by Prime Minister Perry Christie in 2014, demonstrating that some of these issues will be retained. It argues that the Constitution’s exclusionary approach to citizenship creates an incompatibility between the state’s expectation of loyalty of its citizens and the citizens’ ability to identify with the nation.